Efficiency Measurement in Nepalese Non-Life Insurance Companies: A Hybrid Data Envelopment Analysis and Panel Regression Approach - Upadhyaya, Yadav Mani; Budhathoki, Prem Bahadur; Ghimire, Shiva Raj (Nepalese Journal of Insurance and Social Security, 2025)
urpose: This study investigates the operational efficiency of Nepalese non-life insurance companies and examines the key determinants of efficiency, including the impact of recent mergers. Design/methodology/approach: A hybrid methodology is employed. First, a data envelopment analysis (DEA) with variable returns to scale (VRS) evaluates relative efficiency across 14 non-life insurers from 2020 to 2024. Second, panel regression identifies firm-level drivers of efficiency, including profit margin, employee productivity, and investment intensity. Finally, a Difference-in-Differences (DiD) model assesses the effects of the 2023 merger cycle. Findings: The average DEA efficiency score is .80, indicating moderate performance with substantial variation across firms. Profit margin and employee productivity positively influence efficiency, while excessive investment negatively affects performance. The DiD analysis demonstrates that mergers contributed a significant efficiency gain of .09, highlighting the potential benefits of consolidation in the sector. Conclusion: Efficiency in Nepalese non-life insurers is strongly influenced by financial performance, workforce productivity, and prudent capital allocation. Mergers can enhance efficiency, although overinvestment may undermine operational gains Implications: Regulators, managers, and investors can leverage these insights to improve sectoral efficiency, optimize resource allocation, and inform investment and policy decisions. Originality/value: This research integrates DEA, panel regression, and DiD approaches to provide a comprehensive efficiency assessment of Nepalese non-life insurers, offering both methodological rigor and practical relevance. JELClassification : G22, C61, C23, L25